A New Single Phase Single Switched-Capacitor Based Nine-Level Boost Inverter Topology With Reduced Switch Count and Voltage Stress - Siddique, Marif Daula; Mekhilef, Saad; Shah, Noraisyah Mohamed; Sathik Mohamed Ali, Jagabar; Meraj, Mohammad; Iqbal, Atif; Al-Hitmi, Mohammed A. (Institute of Electrical and Electronics Engineers, 2019)
Based on the concept of switched-capacitor based multilevel inverter topology, a new structure for a boost multilevel inverter topology has been recommended in this paper. The proposed topology uses 11 unidirectional switches with a single switched capacitor unit to synthesize nine-level output voltage waveform. Apart from the twice voltage gain, self-voltage balancing of capacitor voltage without any auxiliary method along with reduced voltage stress has been the main advantages of this topology. The merits of proposed topology have been analyzed through various comparison parameters including component counts, voltage stresses, cost and efficiency with a maximum value of 98.3%, together with the integration of switched capacitors into the topology following recent development. Phase disposition pulse width modulation (PD-PWM) technique and nearest level control PWM (NLC-PWM) have been used for the control of switches. Different simulation and hardware results with different operating conditions are included in the paper to demonstrate the performance of the proposed topology. © 2013 IEEE.